2006
DOI: 10.1097/01.nmd.0000208114.79179.7e
|View full text |Cite
|
Sign up to set email alerts
|

Attributional Style in the Eating Disorders

Abstract: Previous research has shown that patients with eating disorders have a characteristic cognitive bias, making internal attributions when evaluating negative events. However, there is less clarity about their attributions for positive events. There are suggestions that this cognitive style might be influenced by depressed mood. This study examines attributional style in the eating disorders for positive and negative events, independent of covariant effects of depression. Twenty-five eating-disordered women and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…Our findings are similar to research on attentional differences in anxious and depressed individuals which shows that these individuals tend to focus more on depressive or threatening stimuli (42, 43), as well as consistent with research on maladaptive attributions for life events in those with eating disorders (12, 44). Similarly, individuals with large degrees of body dissatisfaction may engage in fewer social comparisons with obese individuals, which could lead to a perpetuation of their negative feelings about their bodies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are similar to research on attentional differences in anxious and depressed individuals which shows that these individuals tend to focus more on depressive or threatening stimuli (42, 43), as well as consistent with research on maladaptive attributions for life events in those with eating disorders (12, 44). Similarly, individuals with large degrees of body dissatisfaction may engage in fewer social comparisons with obese individuals, which could lead to a perpetuation of their negative feelings about their bodies.…”
Section: Discussionsupporting
confidence: 90%
“…There are a variety of cognitive biases centered around attention to weight and eating information (e.g., 9, 10, 11), attributions for life events (e.g., 12) which may be related to likelihood of body dissatisfaction and disordered eating [for a review see (13)]. Recent work implicates body image schemas (generalized knowledge structures similar to self-schemas that contain information about one's shape and weight) as a contributing factor in body dissatisfaction because of the way that they direct some individuals' attention toward appearance-related information and stimuli (14-19).…”
Section: Introductionmentioning
confidence: 99%
“…Given that ED patients share the depressive individual's attributional style for negative events (e.g., Morrison, Waller, & Lawson, 2006), the patient who has experienced early and lifelong emotional abuse is likely to attribute these abusive experiences in the ways outlined above-internally ("My parents told me that they hated me because I am unlovable"), globally ("Everyone treated me like dirt"), and stably ("I will never be liked"). Through cognitive restructuring and behavioral experiments (Waller, Kennerly, & Ohanian, 2007), the aim is to help the individual to identify evidence that his/her experiences can be attributed to others, such as the abuser (i.e., external attribution of the negative event), that they apply to a limited element of his/her life (i.e., local attribution), and that they applied in the past but not now (i.e., unstable attribution).…”
Section: Addressing Core Beliefs That Have Developed In Responsementioning
confidence: 97%
“…ED patients responded more with positive weight and shape interpretations when the scenarios related to others. Thus, ED patients judge weight and shape to be a more likely explanation for events with a negative outcome and referring to themselves (Cooper 1997;Morrison et al 2006). Jansen et al (2007) showed that this was also true for overweight and obese children.…”
Section: Interpretation Biasmentioning
confidence: 86%